A novel method for deriving the aerosol hygroscopicity parameter based only on measurements from a humidified nephelometer system - Y. Kuang; C. Zhao; J. Tao; Y. Bian; N. Ma; G. Zhao (Atmospheric Chemistry and Physics, 2017)
Aerosol hygroscopicity is crucial for understanding roles of aerosol particles in atmospheric chemistry and aerosol climate effects. Light-scattering enhancement factor f(RH, λ) is one of the parameters describing aerosol hygroscopicity, which is defined as f(RH, λ) = σsp(RH, λ)∕σsp(dry, λ), where σsp(RH, λ) or σsp(dry, λ) represents σsp at wavelength λ under certain relative humidity (RH) or dry conditions. Traditionally, an overall hygroscopicity parameter κ can be retrieved from measured f(RH, λ), hereinafter referred to as κf(RH), by combining concurrently measured particle number size distribution (PNSD) and mass concentration of black carbon. In this paper, a new method is proposed to directly derive κf(RH) based only on measurements from a three-wavelength humidified nephelometer system. The advantage of this newly proposed approach is that κf(RH) can be estimated without any additional information about PNSD and black carbon. This method is verified with measurements from two different field campaigns. Values of κf(RH) estimated from this new method agree very well with those retrieved by using the traditional method: all points lie near the 1 : 1 line and the square of correlation coefficient between them is 0.99. The verification results demonstrate that this newly proposed method of deriving κf(RH) is applicable at different sites and in seasons of the North China Plain and might also be applicable in other regions around the world.